Comparative Analysis of Muscle Fibers in Selected Muscles of Working and Companion Dog Breeds - Cezary Osiak-Wicha; Katarzyna Kras; Marcin B. Arciszewski (Animals)
The structural and functional characteristics of skeletal muscle fibers play a crucial role in understanding the physical capabilities of dogs, particularly in relation to their breed-specific roles. This study aimed to compare the muscle fiber composition of working and companion dog breeds by analyzing the triceps brachii and biceps femoris muscles, focusing on fiber morphology, myosin heavy chain (MYH) isoform distribution, and nuclei per fiber. A total of 12 dogs, divided equally into working and companion breed groups, were used in this study. Muscle samples were collected post-mortem and prepared for histological analysis using cryosectioning. Immunohistochemical staining was employed to identify the expression of MYH isoforms, including MYH2, MYH4, and MYH7, which correspond to type IIa, IIb, and type I fibers, respectively. The results demonstrated significant differences between the two breed groups. Working dogs exhibited larger muscle fibers, a higher proportion of type IIa (MYH2) and type I (MYH7) fibers, and a greater number of nuclei per fiber, suggesting adaptations for endurance and strength. In contrast, companion dogs showed a higher proportion of type IIb (MYH4) fibers, indicative of their capacity for short bursts of activity rather than sustained exertion. Companion breeds also displayed a higher fiber density but fewer nuclei per fiber, which may contribute to slower muscle regeneration. These findings may provide insights into the muscle adaptations of dogs based on their breed-specific functional demands and highlight the importance of considering these differences in veterinary care and rehabilitation. The study underscores the influence of selective breeding on muscle structure and function in dogs and suggests further research into breed-specific muscle recovery mechanisms.